Od odrzucenia ironii ku jej afirmacji. Dorota Masłowska w poszukiwaniu „my” [From rejection to praise of irony. Dorota Masłowska in her search of “we”] - Claudia Snochowska-Gonzalez (Studia Litteraria et Historica, 2016)
From rejection to praise of irony. Dorota Masłowska in her search of “we”